2019
DOI: 10.20960/nh.02625
|View full text |Cite
|
Sign up to set email alerts
|

Different classification of an adult population by two validated indexes of adherence to the Mediterranean diet.

Abstract: Llamazares JL. Impacto de una adecuada codificación de la desnutrición relacionada con la enfermedad en los índices hospitalarios. Nutr Hosp 2016;33:86-90 Palabras clave: Codificación hospitalaria. Desnutrición. Apoyo nutricional. Gestión de atención al paciente. Diagnóstico. AbstractIntroduction: Disease related malnutrition (DRM) affects at least one in four inpatients, increasing both morbidity and mortality during admission and after discharge. Nevertheless, its repercussion on hospital activity is not pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Regarding the methodology and instruments used, the choice of the diet quality index is one of the most relevant aspects of the study since it establishes the cut-off points on which the conclusions will be drawn. Although diet quality indices are very useful for assessing adherence to dietary patterns in specific populations [ 18 ], there is no universal indicator that can be extrapolated to all populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the methodology and instruments used, the choice of the diet quality index is one of the most relevant aspects of the study since it establishes the cut-off points on which the conclusions will be drawn. Although diet quality indices are very useful for assessing adherence to dietary patterns in specific populations [ 18 ], there is no universal indicator that can be extrapolated to all populations.…”
Section: Discussionmentioning
confidence: 99%
“…Study variables: The variables and categories used for the analyses were as follows: sex (male or female); age groups (16–24 years, 25–44 years, 45–64 years, ≥65 years); country of birth (Spain or others); educational level (no education, primary education, secondary education or higher education); employment status (with full-time or part-time paid work or without paid work which in turn included unemployed persons, students, retired, permanently disabled, engaged in housework and other kinds of economic activity); living with a partner (yes or no); perception of health (good health, which in turn included the responses very good, good and acceptable and bad health which included bad and very bad); leisure-time physical activity (little or none or several times a week) [ 18 ]; sedentary behavior (<2 h/day or ≥2 h/day); hours of screen time per day of television, computer and Internet (>2 h/day or ≤2 h/day) [ 19 ]; smoking (yes, no or ex-smokers); snacking between hours (yes or no), alcohol consumption (no consumption–low-risk consumption, risk consumption or harmful consumption) [ 20 ], arterial hypertension (AHT) (yes or no), myocardial infarction (yes or no), neurological diseases (yes, no) hypercholesterolemia (yes or no), cancer (yes or no), diabetes (yes or no), body mass index (BMI) (underweight, normal weight, overweight or obesity) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Por una parte, se ha visto que la adherencia aumenta con la edad y que puede estar influenciada por factores socioeconómicos y de salud en entornos rurales (20). Respecto a la comparación con otras poblaciones, y pese a que es posible obtener resultados distintos en función del test empleado para valorarla, se han publicado valores de adherencia dentro del mismo rango para varios grupos poblacionales de nuestro país (21).…”
Section: Estilo De Vidaunclassified
“…However, the results of these existing studies are also contradictory in certain cases. As for the adherence to MD, the percentage of subjects in this age group with optimal adherence ranges from 9.5% to 58% [ 24 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Likewise, while some studies have found a clear association between adherence to MD and anthropometric parameters [ 36 , 37 ], this association between variables has not been observed in other research [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%